ORGANIZATION OF INDEPENDENT WORK OF STUDENTS ON THE HISTORY OF PEDAGOGY ON THE BASIS OF COMPARATIVE STUDIES (Pedagogy of Higher and Secondary Education, 2009)
The article reveals some peculiarities in organizing and doing students' independent work with the use of some elements of comparative approach.